Assembling bodies and technologies: a poststructural ethnography of sexualized drug use among gay, bisexual, and other men who have sex with men. (4th May 2021) - Holmes, Dave; Numer, Matthew; Hammond, Chad; Joy, Phillip; Sinno, Jad
Abstract: The identities and communities of gay, bisexual, and other men who have sex with men (GBMSM) are undergoing reconfiguration through two technologies: the digital spaces of social networking and hookup apps, and the sexualized use of chemicals such as recreational and illicit drugs, pharmaceuticals, and steroids. These technologies are creating spaces for GBMSM to indulge in excesses and extremes of pleasure, generating what has been described as an online chemculture. We approached this topic from a poststructuralist queer perspective, attending to the ways in which the fluid assemblages between GBMSM bodies and technologies produce sexual relations that resist heteronormative and other oppressive social structures. Using discourse analysis, this mixed method study (questionnaires and semi-structured interviews) of 50 GBMSM explored how they talked about their sexualized uses of digital and chemical technologies. Data collection occurred in three Canadian cities (Halifax, Ottawa, and Vancouver). The results identify the technologies most frequently employed in the sexual encounters of GBMSM, as well as participants' self-identified purposes for using these technologies and the effects they have on GBMSM identities and communities. This study suggests that there is some potential, though not without some tension, in GBMSM using digital and chemical technologies to realize queer desires.